The repercussions of economic terrorism on Syrian foreign trade during the period (2011-2020) (Damascus University Journal for the economic and Political sciences, 2023)
The research dealt with the study of the repercussions of economic terrorism as a form of unilateral economic sanctions imposed by the United States of America, the European Union and some Arab countries on Syria, especially the foreign trade sector during the period (2011-2020). On the Syrian foreign trade sector during the period (2011-2020), in addition to showing the extent of the Syrian foreign trade sector's contribution to Arab and international trade. In the research, the statistical analysis method was used to study the impact of terrorism on Syrian foreign trade through the Kendall's tau_b correlation coefficient, and the Spearman's rho correlation coefficient, to find out the trend and the degree of relationship between the study variables, and the research concluded that the Syrian foreign trade sector is one of the The sectors most affected by terrorism and economic sanctions, and the study variables have an inverse relationship.
Keywords: Economic sanctions; Syrian foreign trade; Economic terrorism